The lab-to-fab journey of copper-based electrocatalysts for multi-carbon production: Advances, challenges, and opportunities. (February 2021) - Jiao, Shilong; Fu, Xianwei; Zhang, Li; Zhang, Luhong; Ruan, Shuangchen; Zeng, Yu-Jia; Huang, Hongwen
Graphical abstract: Electrochemical reduction of CO2 from the atmosphere that powered by renewable electricity offers cost-competitive method for closing the carbon cycle and realizing carbon-neutral economy. Highlights: Overview of the social-economic benefits and the industrial potential of various C2+ products is offered and compared. Electrocatalyst design, electrolyser design and electrolyte design in the electrochemical reduction of CO2 are comprehensively summarized. The current in-depth understanding of the C2+ pathways and the challenges a in this field are briefly discussed. Abstract: Carbon capture, utilization, and storage (CCUS) is an important emissions reduction technology that can be deployed in the industrial sector and in the power generation. By converting the CO2 in the atmosphere into value-added hydrocarbons with high energy density and ease of transportation and storage, CO2 utilization has witnessed a sharp rise in the amount of public and private spending on R&D programs and projects. Copper has been proved as the only known electrocatalyst that can catalyze the CO2 into hydrocarbons with adequate efficiency and selectivity. In this review, we will begin with an introduction of some background to the electrochemical CO2 reduction reactions (ECR) process. Followed by a discussion of the world's energy status, we then focus on the advances for the optimization of the Cu-based electrocatalysts that generate multi-carbon products to meet the requirements of the industry from the point-view of electrolyzer design, electrocatalysts design and electrolyte design. Afterwards, we highlight the in-depth understanding of the electrocatalytic process combining theoretical methods and in-situ/operando experimental approaches. Finally, we present the challenges by discussing how they can be overcome to achieve a carbon-neutral economy.